Organocatalyzed enantioselective synthesis of 2-amino-5-oxo-5,6,7,8-tetrahydro-4H-chromene-3-carboxylates - Ramireddy, Naresh (2011)
The organocatalyzed enantioselective synthesis of biologically active 2-amino-5-oxo-5,6,7,8-tetrahydro-4H-chromene-3-carboxylate derivatives was achieved using bifunctional cinchona alkaloids as the catalysts. Using quinine thiourea as the catalyst, the tandem Michael addition-cyclization reaction between 1,3-cyclohexanediones and alkylidenecyanoacetate derivatives gives the desired products in high yields (up to 92%) and good ee values (up to 82%).